Evaluating Single and Multi-Species Summer Cover Crops for Biomass Yield - J. K. Farney; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2019)
Cover crops have multiple benefits to integrated agricultural production systems. However, information is needed on best species and mixes to use. In this one-year study, the single species grass cover crops produced the most biomass. Spring forage peas did not perform well as a summer cover crop, yielding the same biomass as the fallow areas. Adding collards to the mixtures generally reduced total biomass production compared to single species of grasses alone. Total biomass production was affected by the number of plants in the mixture. Yields of grass-only plots were ~868 lb of dry matter (DM) per acre more than cover crop mixtures composed of two or three plant species. Plots with cover crop mixes yielded on average 1,348 lb DM/acre more than single species plots with legumes or collards. Grasses composed the greatest proportion of the total biomass (>77% of total DM biomass was from grass species in mixtures).
Keywords: cover crop; summer annual; legumes